Caracterização fenotípica, genômica e transcriptômica de parasitos Crithidia sp. LVH60a obtidos de pacientes diagnosticados com Leishmaniose Visceral - Rogerio, Luana Aparecida (2023)
Leishmaniasis is a group of neglected diseases that can be caused by over 20 species of protozoa from genus Leishmania. Since 1980, monoxenous trypanosomatids have been found in cutaneous and visceral leishmaniasis cases in both immunocompetent and immunocompromised patients. In Brazil, parasites of Crithidia genus were first reported in 2019 in a fatal case of human visceral leishmaniasis in Sergipe (SE), referred to as Crithidia sp. LVH60A. To characterize clinical isolates of Crithidia sp. LVH60A parasites obtained from a relapsing patient from the same region, this study aimed to characterize phenotypically and perform genomic and transcriptomic analyzes of these clinical isolates. In this regard, parasite cultures were analyzed for growth curves, morphological features, in vitro infectivity and in silico identification of virulence-related proteins in Crithidia sp. LVH60A genome. Genomic DNA was sequenced, assembled, and compared to other trypanosomatid species. Additionally, we assessed the difference in gene expression of parasites and human macrophages infected with different species of Leishmania and Crithidia using messenger RNA sequencing (mRNA-seq), employing a dual RNA-seq approach. Phenotypic analyses demonstrated that the Crithidia sp. LVH60A parasites were capable of replicate at temperatures of 25 °C and 35 °C, surviving and multiplying within different macrophage lineages. Morphological analyses revealed that the cellular body of Crithidia sp. LVH60A is rounded, possesses shorter flagella than L. infantum, and presents some differences when compared to the Crithidia fasciculata TCC039E strain. Genomic analyses showed that the clinical isolates from 2017 had over 98% nucleotide identity with the LVH60a C1 strain (Crithidia sp. LVH60A). Genome alignments of Crithidia sp. LVH60A and C. fasciculata strains showed an average nucleotide identity ranging from 92.7% to 94.8%, depending on the software used. Chromosomal rearrangements of Crithidia sp. LVH60A was also observed and validated when compared to C. fasciculata CfCl reference genome. The mRNA-seq results showed that infection with different parasite strains did not significantly alter the transcriptional expression of macrophages; however, slight changes were observed shortly after the infection. However, there was a clear difference in the expression of the trypanosomatid transcripts. Some differentially expressed transcripts are shared by strains of Leishmania spp. and Crithidia sp. LVH60A. These transcripts encode proteins that mediate responses to stress, nutrition, and host immune response evasion. Our results suggest that the Crithidia sp. LVH60A may be a new species within the Crithidia genus; however, more isolates of Crithidia sp. LVH60A need to be analyzed with a focus on population genomics to confirm this evidence.